2022
DOI: 10.1097/jom.0000000000002622
|View full text |Cite
|
Sign up to set email alerts
|

Computer and Furniture Affecting Musculoskeletal Problems and Work Performance in Work From Home During COVID-19 Pandemic

Abstract: Objectives: We surveyed how home-working conditions, specifically furniture and computer use, affected self-reported musculoskeletal problems and work performance. Methods: Questionnaires from 4112 homeworkers were analyzed. The relationship between subjective musculoskeletal problems or work performance and working conditions were determined by logistic regression analyses. Results: More than half the homeworkers used a work desk, work chair, and laptop computer. However, approximately 20% of homeworkers used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These findings were similar to those of a previous cross-sectional study that found no significant difference in the odds ratios for low back pain among teleworkers using a low table compared with those using a work desk/PC desk. 27 The standing desk had the lowest sufficiency rate of 16.1% for the 14 environmental factors, suggesting that those with somatic symptoms, such as shoulder pain and low back pain, may have been aware of the prevention of aggravation and made the necessary environmental arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were similar to those of a previous cross-sectional study that found no significant difference in the odds ratios for low back pain among teleworkers using a low table compared with those using a work desk/PC desk. 27 The standing desk had the lowest sufficiency rate of 16.1% for the 14 environmental factors, suggesting that those with somatic symptoms, such as shoulder pain and low back pain, may have been aware of the prevention of aggravation and made the necessary environmental arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies that identify negative effects of telework. These concern psychological aspects, such as lack of social contact with colleagues, loneliness, disrupted family relationships (Xiao et al, 2021;Bouziri et al, 2020;Galanti et al, 2021;Tejero et al, 2021;Chen, 2022), stress and depression (Tavares, 2017;Galanti et al, 2021;Hayes et al, 2021;Chen, 2022), as well as aspects of physical health, like unhealthy dietary changes (Bouziri et al, 2020;Xiao et al, 2021;Sato et al, 2021;Alah et al, 2022;Griffiths et al, 2022;Ekpanyaskul & Padungtod, 2021;Guler et al, 2021), long periods of sitting in front of a computer screen, weight gain (Suka et al, 2022;Guler et al, 2021;Ekpanyaskul & Padungtod, 2021;Alah et al, 2022), a lack of control over work time duration, often at the expense of sleep time (Bouziri et al, 2020;Alah et al, 2022;Tejero et al, 2021;Ekpanyaskul & Padungtod, 2021), poor working conditions and ergonomics (Argus & Pääsuke, 2021;Ipsen et al, 2021;Du et al, 2022;Ekpanyaskul & Padungtod, 2021) often causing the onset of backpain (Bouziri et al, 2020;Du et al, 2022;Guler et al, 2021) and reduced physical activity (Xiao et al, 2021;Fukushima et al, 2021;Grif...…”
Section: Introductionmentioning
confidence: 99%